Tradições discursivas em anúncios de e sobre moda nos jornais paraibanos do século XIX: relação língua-cultura-sociedade e léxico - Oliveira, Mônica Maria Montenegro de (2011)
This study is consisted of a specific reality of the historical context of Paraíba and the relationship of language-culture-society and lexicon, from the perspective of Discursive Tradition: ads. Based on the ideas of Coseriu, Kabatek, Oesterrecher, Schiliben-lange, among others, the work aimed at identifying, from the study and analysis of the ads of and on fashion, the textual presence of social historic cultural aspects of the language and lexicon, as marks of the movement of social construction in periodicals from Paraíba state. The nineteenth century was established as a time marker of the research, observing the classification and categorization of the topic (issue), specifically by means of fashion with the selection and study of the ads, in particular, the period from 1862 to 1895. The corpus is formed by ads of and on fashion - clothing and accessory - collected from thirteen newspapers from Paraíba state of the determined period: A Imprensa (JI), O Publicador (JPU), O Despertador (JD), O Conservador (JC), Jornal da Parahyba (JJP), O Liberal Parahybano (JLP), O Mercantil (JME), Gazeta da Parahyba (JGP), O Estado da Paraíba (JEdaP), O Estado do Parahyba (JEdoP), O Parahybano (JP), A União(JU) e Gazeta do Comércio (JGC). Such advertisements were collected by employees of the Casa José Américo Foundation and researchers from the Federal University of Paraíba (UFPB), cataloged and published under the organization of Aldridge & Nicolau (2009) at Quem o pretender comprar dirija-se a... coletânea de anúncios paraibanos do século XIX, as part of the History Project of the Brazilian Portuguese (PHPB), which catalogues and studies the history (tradition) of various genres from the colonial era in Brazil. During this particular study, some changes in the ads under the socio historical factors were observed, however, many features have been maintained (retained), for this reason this genre was considered as a discursive tradition. Therefore, the understanding of the construction of the central question of this work was to understand how the ads related to fashion construct meanings, circulate social discourses and show (reveal) cultural and ideological values, a new way of living and thinking. The textual structure and the discursive aspects of the corpus has allowed us to identify the socio-historical-cultural and lexical-semantic relevant aspects to the society of Paraiba state at that time.